Diskriminasi Terhadap Penyandang Disabilitas Pengguna Jasa Angkutan Udara. (Studi Putusan Mahkamah Agung Nomor 439 PK/Pdt/2017) - Yesi Yuliana (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The purpose of this paper is to find out how the fulfillment of accessibility provided by the Government to persons with disabilities, given the acts of discrimination that occurred in Ridwan Sumantri as decided in the Supreme Court ruling Number 439 PK / Pdt / 2017, this case is an example that the government is still unable provide justice to persons with disabilities in using air transport, while injustice in this case can be seen from special facilities not provided by air transport operators as determined by applicable laws and regulations, the type of research used in this study is the type of legal research normative, which is a process to find a rule of law, legal principles, and legal doctrines to address the legal issues being faced. The conclusion of this research is that in writing all persons with disabilities have been determined that each organizer of air transport is obliged to provide all facilities and special personnel to assist persons with disabilities and is given protection to guarantee equal rights, but in practice all of these rules are not yet fully provided by the organizer public transportation.